DIALEKTIKA ANTARA FILSAFAT DAN AGAMA DALAM PEMIKIRAN FILSAFAT ISLAM: Kesinambungan dan Interaksi - Wardani, Wardani (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2014)
This article is aimed to describe dialectical relation between Islamic philosophy (hikmah) and Islamic religious doctrin (syarÃ®âah). The tension between two has emerged since declination of rational theology (Muâtazilite) and since the rise of ortodox theology (Asyâarite). Al-GhazÃ¢lÃ®, one of prominent scholars of the Asyâarite, has attacked Moslem philosophers, such as Ibn SÃ®nÃ¢. This article has came to the conclusion that in such tension, in which religion and rational thought met, the two neither reached utterly different results, nor yet were they identical, but seemed to run parallel to one another.